Fate of soil applied black carbon: downward migration, leaching and soil respiration - Major, J.; Lehmann, Johannes; Rondón, Marco Antonio; Goodale, C (Wiley, 2010)
Black carbon (BC) is an important pool of the global C cycle, because it cycles much more slowly than others and may even be managed for C sequestration. Using stable isotope techniques, we investigated the fate of BC applied to a savanna Oxisol in Colombia at rates of 0, 11.6, 23.2 and 116.1 t BC ha?1, as well as its effect on non-BC soil organic C. During the rainy seasons of 2005 and 2006, soil respiration was measured using soda lime traps, particulate and dissolved organic C (POC and DOC) moving by saturated flow was sampled continuously at 0.15 and 0.3 m, and soil was sampled to 2.0 m. Black C was found below the application depth of 0–0.1 m in the 0.15–0.3 m depth interval, with migration rates of 52.4±14.5, 51.8±18.5 and 378.7±196.9 kg C ha?1 yr?1 (±SE) where 11.6, 23.2 and 116.1 t BC ha?1, respectively, had been applied. Over 2 years after application, 2.2% of BC applied at 23.2 t BC ha?1 was lost by respiration, and an even smaller fraction of 1% was mobilized by percolating water. Carbon from BC moved to a greater extent as DOC than POC. The largest flux of BC from the field (20–53% of applied BC) was not accounted for by our measurements and is assumed to have occurred by surface runoff during intense rain events. Black C caused a 189% increase in aboveground biomass production measured 5 months after application (2.4–4.5 t additional dry biomass ha?1 where BC was applied), and this resulted in greater amounts of non-BC being respired, leached and found in soil for the duration of the experiment. These increases can be quantitatively explained by estimates of greater belowground net primary productivity with BC addition.